A primary care Symptoms Clinic for patients with medically unexplained symptoms: pilot randomised trial. Issue 1 (9th February 2012) - Burton, Christopher; Weller, David; Marsden, Wendy; Worth, Allison; Sharpe, Michael
Abstract : Objectives: To conduct a pilot trial of a primary care Symptoms Clinic for patients with medically unexplained symptoms and evaluate recruitment and retention, and acceptability of the intervention and to estimate potential treatment effects for a full trial. Trial design: Randomised parallel group pilot trial. Setting: Primary care in one locality. Participants: Primary care database and postal questionnaire were used to identify patients with multiple specialist referrals and multiple physical symptoms unlikely to be explained by disease. Interventions: General practitioner (GP) with special interest 'Symptoms Clinic' + usual care versus usual care alone. The Symptoms Clinic comprised one long (1 h) and three short (20 min) appointments. Outcomes: Number of patients identified and recruited; acceptability of the intervention (items from Client Satisfaction Questionnaire and interview); Medical Outcomes Survey Short Form 12 (SF-12) physical component summary. Randomisation: Automated blocked randomisation accessed by telephone. Blinding: None. Numbers randomized: 16 to intervention and 16 to usual care alone. Recruitment: 72 patients, from seven GP practices, had repeated specialist referrals and a Patient Health Questionnaire (PHQ)-15 score of ≥10 indicating a high probability of medically unexplained symptoms. 15 were ineligible and 25 declined to participate. Numbers analysed: 26 patients; two patients randomised to the intervention group were incorrectly included, three patients in the intervention group and one control did not complete outcome measures. Outcome: Most patients randomised to the Symptoms Clinic found the intervention acceptable: eight out of 11 reported the intervention helped them to deal with their problems. The mean difference between groups in SF-12 physical component summary, adjusted for baseline, was 3.8 points (SD 6). Harms: No observed harms. Conclusions: Patients with multiple medically unexplained symptoms can be systematically identified in primary care; a randomised trial comparing the Symptoms Clinic with usual care is feasible and has the potential to show clinically meaningful benefit. Trial registration: ISRCTN63083469.